Spreadsheet vs. multiagent-based simulations in the study of decision making in supply chains. (18th December 2008) - Moyaux, T.; Chaib-draa, B.; D'Amours, S.
A game called the Quebec Wood Supply Game (QWSG) is a role-playing simulation based on the Beer Game for teaching Supply Chain (SC) dynamics, and, in particular, the bullwhip effect. In this context, this paper describes and compares two simulators based on the QWSG which may be used to study decision making and its impact on SC dynamics. We first focus on the direct implementation of the QWSG in a spreadsheet program. This spreadsheet model is the base on which we next build a more complex MultiAgent Based Simulation (MABS) in which JACK™ agents represent companies. Finally, we compare the respective advantages of each simulator. We identify the features of a SC model making a spreadsheet simulation impossible, and those for which a spreadsheet simulation is better, as good as, or worse than MABS.